Constraints on the Electron Acceleration Process in Solar Flare: A Case Study. Issue 20 (11th October 2021) - Li, G.; Wu, X.; Effenberger, F.; Zhao, L.; Lesage, S.; Bian, N.; Wang, L.
Abstract: Combining in situ measurements of energetic electrons and remote sensing observations of hard X‐rays and type III radio bursts, we examine the release times of energetic electrons in the July 23, 2016 event. We find that the releases of in situ energetic electrons from the Sun are delayed from those electrons that are responsible for the hard X‐rays. We further find that the release time of in situ electrons is a function of electron energy. Under the assumption that the acceleration mechanism for the upward propagating electrons is of Fermi‐type and is controlled by an energy‐dependent diffusion coefficient, we fit these release times by a simple functional form, related to the turbulence spectral index. Implications of our study on the underlying electron acceleration mechanisms and the magnetic reconnection process in solar flares are discussed. Our results demonstrate the power of the recently developed fractional velocity dispersion analysis (FVDA) method in solar flare studies. Plain Language Summary: Solar flares are efficient particle accelerators. Electrons and ions are accelerated to very high energies at solar flares. Magnetic reconnection is believed to be the main energy convertor at solar flares. Observations and simulations in the past decade have shown that when magnetic reconnection occurs, electrons can be accelerated at both the reconnection site and the reconnection exhausts, which are plasma shooting away from the reconnection site. Energetic electrons precipitating down on the solar surface will cause hard X‐ray and gamma ray. Energetic electrons escape outward can be observed in situ. Are these two populations of electron released at the same reconnection site, or they have different acceleration history, perhaps at the two oppositely propagating exhausts? In this study, we examine this question using timing studies of in‐situ electrons and hard X‐ray observations of the solar flare from Fermi observation. We show that outward propagating electrons are undergoing a longer acceleration process than those downward propagating electrons, suggesting an acceleration process that is volume‐filling and is consistent with a second‐order Fermi acceleration at the reconnection exhaust propagating upward. Key Points: Release of in situ electrons at the Sun is delayed from the release of hard X‐ray generating electrons in impulsive SEP events The release delay of in‐situ electrons at the Sun shows a clear energy dependence which can be fitted by a power law of electron momentum The power law index from the above fitting is related to the turbulence dissipation range spectral index at the flare site